2020
DOI: 10.9734/ajess/2020/v11i330294
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Junior High School Pupils Face in the Use of Information and Communication Technology (ICT) Tools for Learning in Ghana

Abstract: Aims: This paper seeks to explore the challenges Junior High School pupils in the South Tongu District in the Volta Region of Ghana face in the use of Information and Communication Technology tools for learning. The rationale was to identify the challenges these pupils face in the use of ICT tools for learning and the possible means to overcome these challenges in the school. Research Design: To achieve the purpose of this studya descriptive research design was used. Place and Duration of Study: Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Similarly, Basri et al (2018) found in a study that there exists a relationship between ICT adoption and academic performance in a conservative environment which resulted to the improvement of the performance of female students. However, Banji et al (2020) identified that the commonest challenges of using ICT tools for learning were lack of opportunity provided by teachers for students to use the tools on their own, inadequate ICT tools and difficulty teaching ICT practical lessons without demonstration. To this, Tanveer (2011) assert that it is critical that both teachers and students develop confidence in using technology through appropriate facilitation using the necessary electronic equipment, training, and time resources.…”
Section: Students' Knowledge and Skills In Ictmentioning
confidence: 99%
“…Similarly, Basri et al (2018) found in a study that there exists a relationship between ICT adoption and academic performance in a conservative environment which resulted to the improvement of the performance of female students. However, Banji et al (2020) identified that the commonest challenges of using ICT tools for learning were lack of opportunity provided by teachers for students to use the tools on their own, inadequate ICT tools and difficulty teaching ICT practical lessons without demonstration. To this, Tanveer (2011) assert that it is critical that both teachers and students develop confidence in using technology through appropriate facilitation using the necessary electronic equipment, training, and time resources.…”
Section: Students' Knowledge and Skills In Ictmentioning
confidence: 99%
“…2020). Education reform policies of government has focused on equal access and quality of education using ICTs, this necessitates the awareness of ICTs in senior secondary school in Delta State through use of ICTs and equipping secondary schools teachers with enhanced skills to teach the senior secondary students in the 21 st century, these will bring awareness of ICTs to senior secondary school students in Delta State [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…So you don't have to open books one by one to find answers or knowledge. Simply by typing keywords in the school library database or on a search engine, and you can find the desired answer [7]. The most important thing is a more practical and structured system management Not only facilitating and improving existing learning systems, ICT also makes administrative system management in schools more practical and structured [8].…”
Section: Introductionmentioning
confidence: 99%